Determination of the IC50 Value of Allivum sativum Methanolic Extract Against Aeromonas hydrophila (Journal of Biochemistry, Microbiology and Biotechnology, 2018)
There are numerous studies done on the efficacy of plant extracts as inhibition agents of bacteria. Several of these studies, however, did not report on the benchmark the concentration of toxicant that causes 50% inhibition or IC50 values, which would allow for comparison with other studies to be made. One of the most accurate ways to measure this value is through analysis of the data using nonlinear regression analysis, where the four parameter logistics equation is routinely employed by many researchers. The aim of this study is to use the four-parameter logistics equation to determine the IC50 value and its confidence interval for the plant extract Allium sativum against the pathogen Aeromonas hydrophila. The result of the fitting gave an IC50 value of 18.78 mg (95% confidence interval of 17.53 to 20.13) with a correlation coefficient value of 0.95, indicating acceptable fitting.
Keywords: IC50 value, Antibacterial, four parameter logistics equation , Aeromonas hydrophila, Allium sativum